Economic and organizational preconditions for the development of agency relations in a crisis period - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V.; Кібік, Ольга Миколаївна; Кібік, О. М.; Кибик, Ольга Николаевна; Kibik, Olha M.; Kivalov, Sergey; Kibik, Olha (Baltija Publishing, 2019)
The purpose of the article is the research of economic-legal and organizational principles of problem solution of economic agents’ functioning and implementation of activities within the system of anti-crisis measures in order to ensure the effective functioning of the country’s economic system. Crisis phenomena change the living tendencies of any economic agent. The purpose of each economic agent is to create sufficient capacity for functioning and development in favourable and especially in crisis conditions. In order to ensure the effective development of a business entity as an economic agent, the main condition is the maximization of its value by increasing the investment attractiveness and level of competitiveness in the domestic and foreign markets. Formation of this condition is a prerequisite for survival in a crisis situation and development ensuring in favourable circumstances. The elements of anti-crisis management should be correctly integrated into the general policy of the management system of economic agents at the microeconomic and macroeconomic level. The subject of the study is the functioning of economic agents in a crisis. Research methodology. The study is based on the use of general scientific and special-scientific methods of scientific knowledge. The dialectical method allowed investigating the definition of agency relations. The method of system analysis was used to study the principles and economic and legal preconditions of the functioning of the anti-crisis management systems. The system-structural method helped to study basic pre-crisis measures to develop crisis-response potential of maritime agency service. Practical implications. The article considers the mechanism of economic and legal provision of anti-crisis management drawing on the example of maritime agents. The most significant components of the transaction costs of the principal are determined. Value/originality. The role of maritime agents’ associations has been identified. The necessity and preconditions for accelerating the adaptation of the world experience of the functioning of self-regulated organizations in the field of the maritime agency, in order to improve the state of the majority of economic entities, is proved. The development of cluster forms of the organization of interaction of different participants in maritime activity was determined as a positive trend. The promising area for further research is the formation of a model of responsible relationships between economic agents of different levels in order to achieve optimal results of realization of individual and social economic interests at key stages of the life cycle of the economic systems functioning.

Метою статті є дослідження економіко-правових та організаційних засад вирішення проблем функціонування суб’єктів господарювання та здійснення діяльності в системі антикризових заходів з метою забезпечення ефективного функціонування економічної системи країни. Кризові явища змінюють життєві тенденції будь-якого економічного агента. Метою кожного економічного агента є створення достатнього потенціалу для функціонування та розвитку в сприятливих і особливо кризових умовах. Для забезпечення ефективного розвитку суб’єкта господарювання як економічного агента головною умовою є максимізація його вартості за рахунок підвищення інвестиційної привабливості та рівня конкурентоспроможності на внутрішньому та зовнішньому ринках. Формування цього стану є передумовою виживання в кризовій ситуації та забезпечення розвитку за сприятливих обставин. Елементи антикризового управління мають бути правильно інтегровані в загальну політику системи управління економічними суб’єктами на мікроекономічному та макроекономічному рівнях. Предметом дослідження є функціонування економічних агентів в умовах кризи. Методологія дослідження. В основі дослідження лежить використання загальнонаукових та спеціально-наукових методів наукового пізнання. Діалектичний метод дозволив дослідити визначення агентських відносин. Методом системного аналізу досліджено принципи та економіко-правові передумови функціонування систем антикризового управління. Системно-структурний метод допоміг дослідити основні докризові заходи щодо розвитку кризового потенціалу морської агентської служби. Практичні наслідки. У статті розглянуто механізм економіко-правового забезпечення антикризового управління на прикладі морських агентів. Визначено найбільш значущі складові трансакційних витрат комітента. Цінність/оригінальність. Визначено роль асоціацій морських агентів. Доведено необхідність та передумови прискорення адаптації світового досвіду функціонування саморегульованих організацій у сфері морського агентства з метою покращення стану більшості суб’єктів господарювання. Позитивною тенденцією визначено розвиток кластерних форм організації взаємодії різних учасників морської діяльності. Перспективним напрямом подальших досліджень є формування моделі відповідальних взаємовідносин економічних суб'єктів різних рівнів з метою досягнення оптимальних результатів реалізації індивідуальних та соціально-економічних інтересів на ключових етапах життєвого циклу функціонування економічних систем.
Kivalov S. Economic and organizational preconditions for the development of agency relations in a crisis period / S. Kivalov , O. Kibik // Baltic Journal of Economic Studies. - Baltija Publishing, 2019. - Vol. 5. - Issue 2. - Р. 73-79.
Keywords: agent; agency relations; maritime agent; anti-crisis management; агент; агентські відносини; морський агент; антикризове управління; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES::Business and economics